Hypofractionated Irradiation Suppressed the Off-Target Mouse Hepatocarcinoma Growth by Inhibiting Myeloid-Derived Suppressor Cell-Mediated Immune Suppression - Chen, Junying; Wang, Zeng; Ding, Yuxiong; Huang, Fei; Huang, Weikang; Lan, Ruilong; Chen, Ruiqing; Wu, Bing; Fu, Lengxi; Yang, Yunhua; Liu, Jun; Hong, Jinsheng; et al. (Frontiers in Oncology, 2020)
Background: Stereotactic radiotherapy treats hepatocellular carcinoma (HCC) at different stages effectively and safely. Besides its direct killing cancer cells, radiotherapy stimulates host immunity against hepatoma. However, the role of myeloid-derived suppressor cells (MDSCs) in on-target and off-target anti-HCC effect induced by hypofractionated irradiation (IR) is unclear. Methods and materials: Hepa1-6 or H22 allogeneic primary tumors in the hind limbs of C57BL/6 or ICR mice were irradiated with 0, 2.5, 4, 6 or 8 Gy/fraction until total dose reached 40 Gy. The off-target effect induced by the IR was investigated by subsequently inoculating the same HCC cells subcutaneously on the abdomen. MDSCs in peripheral blood and tumor tissues were measured by flow cytometry or immunofluorescence microscopy analysis. IL-6, RANTES and G-CSF in irradiated mouse plasma and hepatoma cell cultures were measured with ELISA kits. Conditional media (CM) from irradiated HCC cell cultures on bone marrow cells differentiation and MDSCs proliferation were examined by co-culture and flow cytometry. Results: The anti-tumor immunity triggered by irradiated HCC grown on hind limbs to induce “in-situ tumor vaccine”. It was capable to suppress the growth of HCC implanted subcutaneously on abdomen with Hepa1-6 or H22 cells, accompanying with reduced MDSCs both in blood and tumors. The decreased MDSCs were associated with lower plasma levels of IL-6, RANTES and G-CSF. The cytokines IL-6, RANTES in the CM were lower in high single IR dose group than in control groups but G-CSF was higher. CM from high single dose IR-Hepa1-6 cells reduced the differentiation of C57BL/6 mouse bone marrow cells into MDSCs, while CM from high single dose IR-H22 cells reduced the proliferation of MDSCs, which might be due to the decreased p-STAT3 in bone marrow cells. Conclusions: The hypofractionated IR exerts the strong anti-tumor and abscopal effects via the reduction of MDSCs and its generation of IL-6, RANTES and G-CSF.